Brucella melitensis Wzm/Wzt System: Changes in the Bacterial Envelope Lead to Improved Rev1Δwzm Vaccine Properties - Mena-Bueno, Sara; Poveda-Urkixo, Irati; Irazoki, Oihane; Palacios, Leyre; Cava, Felipe; Zabalza-Baranguá, Ana; Grilló, María Jesús (Frontiers in Microbiology, 2022)
The lipopolysaccharide (LPS) O-polysaccharide (O-PS) is the main virulence factor in Brucella. After synthesis in the cytoplasmic membrane, O-PS is exported to the periplasm by the Wzm/Wzt system, where it is assembled into a LPS. This translocation also engages a bactoprenol carrier required for further biosynthesis pathways, such as cell wall biogenesis. Targeting O-PS export by blockage holds great potential for vaccine development, but little is known about the biological implications of each Wzm/Wzt moiety. To improve this knowledge and to elucidate its potential application as a vaccine, we constructed and studied wzm/wzt single- and double-deletion mutants, using the attenuated strain Brucella melitensis Rev1 as the parental strain. This allowed us to describe the composition of Brucella peptidoglycan for the first time. We observed that these mutants lack external O-PS yet trigger changes in genetic transcription and in phenotypic properties associated with the outer membrane and cell wall. The three mutants are highly attenuated; unexpectedly, Rev1Δwzm also excels as an immunogenic and effective vaccine against B. melitensis and Brucella ovis in mice, revealing that low persistence is not at odds with efficacy. Rev1Δwzm is attenuated in BeWo trophoblasts, does not infect mouse placentas, and is safe in pregnant ewes. Overall, these attributes and the minimal serological interference induced in sheep make Rev1Δwzm a highly promising vaccine candidate.